Underlying mechanism of subcortical brain protection during hypoxia and reoxygenation in a sheep model - Influence of α1-adrenergic signalling. - René Schiffner; Sabine Juliane Bischoff; Thomas Lehmann; Florian Rakers; Sven Rupprecht; Georg Matziolis; Harald Schubert; Matthias Schwab; Otmar Huber; Cornelius Lemke; Martin Schmidt (PLoS ONE, 2018)
While the cerebral autoregulation sufficiently protects subcortical brain regions during hypoxia or asphyxia, the cerebral cortex is not as adequately protected, which suggests that regulation of the cerebral blood flow (CBF) is area-specific. Hypoxia was induced by inhalation of 5% oxygen, for reoxygenation 100% oxygen was used. Cortical and subcortical CBF (by laser Doppler flowmetry), blood gases, mean arterial blood pressure (MABP), heart rate and renal blood flow were constantly monitored. Low dosed urapidil was used for α1A-adrenergic receptor blockade. Western blotting was used to determine adrenergic receptor signalling mediators in brain arterioles. During hypoxia cortical CBF decreased to 72 ± 11% (mean reduction 11 ± 3%, p < 0.001) of baseline, whereas subcortical CBF increased to 168±18% (mean increase 43 ± 5%, p < 0.001). Reoxygenation led to peak CBF of 194 ± 27% in the subcortex, and restored cortical CBF. α1A-Adrenergic blockade led to minor changes in cortical CBF, but massively reduced subcortical CBF during hypoxia and reoxygenation-almost aligning CBF in both brain regions. Correlation analyses revealed that α1A-adrenergic blockade renders all CBF-responses pressure-passive during hypoxia and reoxygenation, and confirmed the necessity of α1A-adrenergic signalling for coupling of CBF-responses to oxygen saturation. Expression levels and activation state of key signalling-mediators of α1-receptors (NOSs, CREB, ERK1/2) did not differ between cortex and subcortex. The dichotomy between subcortical and cortical CBF during hypoxia and reoxygenation critically depends on α1A-adrenergic receptors, but not on differential expression of signalling-mediators: signalling through the α1A-subtype is a prerequisite for cortical/subcortical redistribution of CBF.